THE ANALYSIS OF PROFITABILITY AND LEVERAGE IMPACT TOWARDS RISK DISCLOSURE: A STUDY OF BANKING SECTOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) - Christina, Christina B1034161002 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2020)
ABSTRACT     The study about Risk Disclosure had been studied by many researchers in their study. Researchers want to know the factors that affected the existence of Risk Disclosure. This study was condusted to examine the effect of the Profitability and Leverage toward Risk Disclosure of the Banking Sector Company that listed in Indonesia Stock Exchange (IDX).     This study was aim to describe the effect of the Profitability and Leverage ratio towards the Risk Disclosure of the Banking Sector Company that listed in Indonesia Stock Exchange (IDX). The sample that were taken in this study consist of 44 samples that has been taken from Indonesia Stock Exchange’s website. The Profitability such as Return on Asset (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) and Leverage such as Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) that were used as the independent variables to determine the effect towards the Risk Disclosure. The analysis method that were used was multiple regression analysis and using Microsoft Excel and SPSS 23 as the tool of analysis.     The result of the study showed that from the five independent variables, only one of them have a significant effect, meanwhile the other independent variable has no significant effect. Net Profit Margin (NPM) have a significant effect to the Risk Disclosure at the 5% level of significance. Return on Asset (ROA), Return on Equity (ROE), Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER) has no significant effect towards Risk Disclosure.Keywords : Risk Disclosure, Profitability, Leverage, Return on Asset, Return on Equity, Net Profit Margin, Debt to Asset Ratio, and  Debt to Equity Ratio  REFERENCESAgnes, S. (2005). Analisis Kinerja Keuangan dan Perencanaan Keuangan Perusahaan. Jakarta: PT. Gramedia Pustaka.Agus, R. S. (2010). Manajemen Keuangan Teori dan Aplikasi (Keempat ed.). Yogyakarta: BPFE.Anindyarta, A. W., & Nur, C. (2013). Pengaruh Karakteristik Perusahaan Terhadap Tingkat Pengungkapan Risiko. Diponegoro Journal of Accounting, 2(3), 1-14.Baridwan, Z. (1992). Intermediate Accounting (Tujuh ed.). Yogyakarta: Yogtakarta.Brigham, E. F., & Houston, J. F. (2014). Dasar-dasar Manajemen Keuangan. Jakarta: Salemba Empat.Brigham, E. F., & Joel, F. H. (2001). Manajemen Keuangan (Vol. 1). Jakarta: Erlangga.Bursa Efek Indonesia. (2019, 09 10). Retrieved from www.idx.co.idDeegan, C. (2004). Financial Accounting Theory. Sydney: McGraw-Hill.Eisenhardt, K. (1989). Agency Theory: An Assesment and Review. Academy of Management Riview, 57-74.Fahmi, I. (2011). Analisa Laporan Keuangan. Bandung: Alfabeta.Freeman, R. E., & McVea, J. (2001). A Stakeholder Approach to Strategic Management. Darden Business School Working Paper. Retrieved from https://papers.ssrn.com/sol3/papers.cfm?abstract_id=263511Ghozali, I. (2016). Aplikasi Analisis Multivariete Dengan Program IBM SPSS 23 (8 ed.). Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, I. (2016). Aplikasi Analisis Multivariete Dengan Program IBM SPSS 23 (8 ed.). Semarang: Badan Penerbit Universitas Diponegoro.Hanafi, M. M., & Hakim, A. (2012). Analisis Laporan Keuangan (Keempat ed.). Yogyakarta: UPP STIM YKPN.Hanafiah, R. (2014). The Influence Of Firm Size, Type Of Industry, The Level Of Leverage, And Profitability To Risk Disclosure (Empirical Studies On The Annual Report Non-Financial Companies Listed On The Indonesia Stock Exchange In 2007-2011). Jurnal Ekonomi, 2(2), 42-66.Harahap, S. S. (2009). Teori Kritis Laporan Keuangan. Jakarta: Bumi Aksara.Ikatan Akuntan Indonesia (IAI). (2015). Pernyataan Standar Akuntansi Keuangan (PSAK) No 60 Instrumen Keuangan: Pengungkapan. Jakarta: IAI.Irawati, S. (2006). Manajemen Keuangan. Bandung: Pustaka.Jensen, & Meckling. (1976). Theory of the Firm: Managerial Behavior, Agency Cost and Ownership Structure. Journal of Financial Economics, 3(4), 305-360.Kasiram, M. (2008). Metodologi Penelitian. Malang: UIN-Malang Pers.Kasmir. (2008). Analisis Laporan Keuangan. Jakarta: Raja Grafindo Persada.Kasmir. (2012). Analisis Laporan Keuangan (Ke-2 ed.). Jakarta: PT Raja Grafindo Persada.Kasmir. (2013). Analisis Laporan Keuangan. Jakarta: Rajawali Pers.Layyinatusy, S. (2013). Determinan Pengungkapan Enterprise Risk Management pada Perusahaan Manufaktur di Indonesia. Accounting Analysis Journal(2252-6765), 286-294. Retrieved from http://journal.unnes.ac.id/sju/index.php/aajMeilani, S. E., & Wiyadi. (2017). Determinan Financial Risk Disclosure: Studi Pada Perusahaan yang Terdaftar dalam Morgan Stanley Capital International (MSCI) Indonesia Index Periode 2014-2016. Jurnal Ekonomi Manajemen Sumber Daya, 19(2), 119-134.Nahar, S., Azim, M., & Jubb, C. A. (2016). Risk disclosure, cost of capital and bank performance. International Journal of Accounting & Information Management, 24(4), 476-494. Retrieved from https://doi.org/10.1108/IJAIM-02-2016-0016Notoatmodjo, S. (2005). Methodologi Penelitian . Jakarta: PT. Rineka Cipta.Rosalina, D. (2017, March 19). kontan. Retrieved September 27, 2019, from Kontan.co.id: https://keuangan.kontan.co.id/news/pembobolan-bankSarwono, A. A., Hapsari, D. W., & Nurbaiti, A. (2018). Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Pengungkapan Manajemen Risiko. e-Proceeding of Management, 5(1), 769-777.Scott, W. R. (2015). Financial Accounting Theory (Seventh ed.). United States: Canada Cataloguing.Spence, M. (1973). Job Market Signaling. The Quarterly Journal of Economics, 87(3), 355-374.Sugiyono. (2005). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Sugiyono. (2008). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Sulistyaningsih, & Gunawan, B. (2016). Analisis Faktor-faktor yang Memengaruhi Risk Management Disclosure. Riset Akuntansi dan Kauangan, 1(1), 1-11.Susanti, R. D., Isbanah, Y., & Kusumaningrum, T. M. (2018). Pengaruh Kepemilikan Publik, Ukuran Perusahaan, Leverage dan Profitabilitas terhadap Risk Management Disclosure pada Bank Konvensional di BEI Periode 2012-2016. Seminar Nasional Manajemen dan Bisnis ke-3, 503-514.Syafitri, N. Y., Majidah, & Dillak, V. J. (2016). Pengungkapan Risiko Perusahaan: Karakteristik Perusahaan dan Corporate Governance. e-Proceeding of Management, 3(3).Syamsuddin. (2006). Manajemen Keuangan Perusahaan. Jakarta: PT Raja Grafindo Persada.Tauringana, V., & Chithambo, L. (2016). Determinants of risk disclosure compliance in Malawi: a mixed-method approach. Journal of Accounting in Emerging Economies, 6(2), 111-137. doi:10.1108/JAEE-03-2014-0015Wicaksono, S. A., & Adiwibowo, A. S. (2017). Analisis Determinan Pengungkapan Risiko (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015). Diponegoro Journal of Accounting, 6(4), 1-14. Retrieved from http://ejournal-s1.undip.ac.id/index.php/accounting